2021
DOI: 10.1149/2162-8777/abe7aa
|View full text |Cite
|
Sign up to set email alerts
|

Role of Molecular Structure on Modulating the Interfacial Dynamics for Shallow Trench Isolation (STI) Chemical Mechanical Planarization (CMP) Applications

Abstract: As feature sizes continue to shrink well beyond the 7 nm node, understanding the delicate balance present in the chemical mechanical planarization (CMP) process is of utmost importance. In order to achieve high through-put and defect-free CMP processes it is critical to develop predictive analytical techniques that directly correlate to macroscopic STI CMP performance metrics (i.e. oxide/nitride removal, defectivity, and dishing/erosion). This work employed a suite of techniques to monitor the CeO2 nanoparticl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
(45 reference statements)
0
7
0
Order By: Relevance
“…In the case of SC-1, it was determined that the generation of ROS is crucial to the effective removal of the CeO 2 from the surface of the wafer as it helps convert the surface oxidation state from Ce 3+ to Ce 4+ . This conversion in the surface redox state will aid in the weakening of the surface ceria–silanol bond resulting in the effective removal under reduced shear force conditions. , Therefore, it would be beneficial to take the “soft” cleaning nature of the supramolecular structures and couple them with ROS to maximize particle removal. Specifically, this work will look at incorporating Cu 2+ –amino acid complexes as they are known to aid in the production of • OH through catalytic Fenton chemistry.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of SC-1, it was determined that the generation of ROS is crucial to the effective removal of the CeO 2 from the surface of the wafer as it helps convert the surface oxidation state from Ce 3+ to Ce 4+ . This conversion in the surface redox state will aid in the weakening of the surface ceria–silanol bond resulting in the effective removal under reduced shear force conditions. , Therefore, it would be beneficial to take the “soft” cleaning nature of the supramolecular structures and couple them with ROS to maximize particle removal. Specifically, this work will look at incorporating Cu 2+ –amino acid complexes as they are known to aid in the production of • OH through catalytic Fenton chemistry.…”
Section: Resultsmentioning
confidence: 99%
“…With device feature size and complexity continuing to approach the 3 nm node, limiting induced defectivity during not only the polishing process but also the post-chemical mechanical planarization (p-CMP) process is of utmost importance. To effectively achieve this, an understanding of the interactions between the slurry residue and cleaning formulations at the molecular level is crucial. Traditional p-CMP processes for STI involve a contact method of cleaning through PVA brush scrubbing. This contact method has been coupled with different cleaning chemistry types, such as redox additives and surfactants, to effectively remove residual CeO 2 nanoparticles on the surface. , It has been widely accepted that the particle left on the TEOS wafer post-polish is predominantly Ce 3+ as the presence of surface oxygen vacancies is critical during the polishing step. , This strong noncovalent interaction between the CeO 2 nanoparticle and wafer surface means that the cleaning chemistries used in the p-CMP process require a redox-active cleaning environment so that the particle can be removed via the charge flipping mechanism (i.e., converting Ce 3+ to Ce 4+ ). While this has shown to be an effective mode of particle removal, there is an increase in the process shear force (mechanical component), which results in secondary defect formation (i.e., increased scratching/surface roughness). , More recently attention has shifted to developing p-CMP cleaning formulations that employ encapsulation of the CeO 2 nanoparticle using supramolecular chemistries (i.e., surfactants, polyelectrolytes, liposomes, etc.).…”
Section: Introductionmentioning
confidence: 99%
“…38 Types and amounts of oxygen scavengers should be chosen carefully in consideration of the interaction with other slurry components since the complex interactions between slurry components determine the physicochemical properties of slurry such as abrasive particle size and distribution, surface chemistry, dispersion stability, and rheological behavior and their CMP performance. 39…”
Section: Resultsmentioning
confidence: 99%
“…Several published reports have shown that high oxide polish rate slurries can be obtained in the presence of additives by stabilizing Ce 3+ on the ceria surface, 51,52 but detailed information was not provided in most cases. The possible mechanism of high SiO 2 RR was hinted at in a few papers, 53,54 which implies a change in the redox state of Ce by the transfer of hydrogen/oxygen atoms between the organic additives and the ceria surface. So carefully selecting additives and their combination with the particles is very important in preparing highperformance ceria-based CMP slurries.…”
Section: Future Research Needs and Prospectsmentioning
confidence: 99%